Worldwide genetic variation at the 3 ' untranslated region of the HLA-G gene: balancing selection influencing genetic diversity - Sabbagh, A.; Luisi, P.; Castelli, Erick da Cruz [UNESP]; Gineau, L.; Courtin, D.; Milet, J.; Massaro, J. D.; Laayouni, H.; Moreau, P.; Donadi, E. A.; Garcia, A. (Nature Publishing Group, 2014)
The HLA-G (human leukocyte antigen-G) molecule plays a pivotal role in immune tolerance by inhibiting different cell subsets involved in both innate and adaptive immunity. Besides its primary function in maintaining the maternal-fetal tolerance, HLA-G has been involved in a wide range of pathological conditions where it can be either favorable or detrimental to the patient, depending on the nature of the pathology. Although several studies have demonstrated the utmost importance of the 30 untranslated region (3'UTR) in the HLA-G expression profile, limited data exist on the sequence variability of this gene region in human populations. In this study, we characterized the genetic diversity and haplotype structure of the HLA-G 3'UTR by resequencing 444 individuals from three sub-Saharan African populations and retrieving data from the 1000 Genomes project and the literature. A total of 1936 individuals representing 21 worldwide populations were combined and jointly analyzed. Our data revealed a high level of nucleotide diversity, an excess of intermediate frequency variants and an extremely low population differentiation, strongly supporting a history of balancing selection at this locus. The 14-bp insertion/deletion polymorphism was further pointed out as the likely target of selection, emphasizing its potential role in the post-transcriptional regulation of HLA-G expression.
Keywords: HLA-G; 3 ' UTR; haplotype; linkage disequilibrium; balancing selection; evolution